Metastatic and non-metastatic sentinel inguinofemoral lymph nodes in vulvar cancer show an increased lymphangiogenesis - Magda Piechowicz; Marcin Mikos; Tomasz Banas; Krzysztof Okon; Milosz Pietrus; Marta Balajewicz-Nowak; Lukasz Szczudlik; Zbigniew Kojs; Aleksandra Czerw; Grzegorz Juszczyk; Kazimierz Pityński (Annals of Agricultural and Environmental Medicine, 2020)
Introduction and objective Lymph node involvement is a strong predictor of disease recurrence and patient survival in vulvar cancer. The aim of the study was to evaluate the feasibility of sentinel lymph node (SLN) screening, the incidence of skip metastases, and lymph node lymphangiogenesis.